Plantaricins markedly enhance the effects of traditional antibiotics against Staphylococcus epidermidis. (16th January 2019) - Selegård, Robert; Musa, Amani; Nyström, Pontus; Aili, Daniel; Bengtsson, Torbjörn; Khalaf, Hazem
Aim: Bacteriocins are considered as promising alternatives to antibiotics against infections. In this study, the plantaricins (Pln) A, E, F, J and K were investigated for their antimicrobial activity against Staphylococcus epidermidis .Materials & methods: The effects on membrane integrity were studied using liposomes and viable bacteria, respectively.Results: We show that PlnEF and PlnJK caused rapid and significant lysis of S. epidermidis, and induced lysis of liposomes. The PlnEF and PlnJK displayed similar mechanisms by targeting and disrupting the bacterial cell membrane. Interestingly, Pln enhanced the effects of different antibiotics by 30- to 500-fold.Conclusion: This study shows that Pln in combination with low concentrations of antibiotics is efficient against S. epidermidis and may be developed as potential treatment of infections.